2016
DOI: 10.1371/journal.ppat.1005734
|View full text |Cite
|
Sign up to set email alerts
|

A Putative Small Solute Transporter Is Responsible for the Secretion of G377 and TRAP-Containing Secretory Vesicles during Plasmodium Gamete Egress and Sporozoite Motility

Abstract: Regulated protein secretion is required for malaria parasite life cycle progression and transmission between the mammalian host and mosquito vector. During transmission from the host to the vector, exocytosis of highly specialised secretory vesicles, such as osmiophilic bodies, is key to the dissolution of the red blood cell and parasitophorous vacuole membranes enabling gamete egress. The positioning of adhesins from the TRAP family, from micronemes to the sporozoite surface, is essential for gliding motility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 64 publications
0
76
0
Order By: Relevance
“…By using anti-GFP antibodies in fixed sporozoites, we were not able to detect GFP-TRP1∆N on the sporozoite surface (Figure 7—figure supplement 1). Comparison of the localizations of TRP1-GFP and GFP-TRAP (Kehrer et al, 2016b) showed that the two proteins were localized differently (Figure 8). While GFP-TRAP appears mostly localized to micronemes at the front end of the sporozoite, TRP1-GFP appears to localize in what might be a subset of micronemes or a different organelle that does not extend all the way to the front.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By using anti-GFP antibodies in fixed sporozoites, we were not able to detect GFP-TRP1∆N on the sporozoite surface (Figure 7—figure supplement 1). Comparison of the localizations of TRP1-GFP and GFP-TRAP (Kehrer et al, 2016b) showed that the two proteins were localized differently (Figure 8). While GFP-TRAP appears mostly localized to micronemes at the front end of the sporozoite, TRP1-GFP appears to localize in what might be a subset of micronemes or a different organelle that does not extend all the way to the front.…”
Section: Resultsmentioning
confidence: 99%
“…Parasites that lack proteins involved in gliding motility (TRAP and CPβ) do not enter into salivary glands (Sultan et al, 1997; Ganter et al, 2009) and decreased gliding motility (S6/TREP/UOS3, Coronin, CSP and PAT) often goes along with decreased salivary gland invasion (Coppi et al, 2011; Kehrer et al, 2016b; Steinbuechel and Matuschewski, 2009; Combe et al, 2009; Bane et al, 2016; Tewari et al, 2002; Mikolajczak et al, 2008). Hence parasites that lack proteins involved in both egress and motility are also impaired in salivary gland invasion and thus these proteins are essential for life cycle progression at two subsequent steps.…”
Section: Discussionmentioning
confidence: 99%
“…A GFP-tagged version of TFP1 localised to the surface of the asexual intraerythrocytic parasite when expressed from an episomal plasmid and under the control of a non-endogenous promoter (Augagneur et al, 2013). However, when expressed from its native locus and promoter, GFP-tagged TFP1 was not evident in asexual blood-stage parasites and the recombinant transporter was instead localised to the osmiophilic body of gametocytes and the micronemes and surface of sporozoites (Kehrer et al, 2016). Moreover, tfp1 was shown to be dispensable in the asexual blood stage, but was essential for infecting mosquitos -and this knockout phenotype was rescued by mCherry-tagged TFP1 (Kehrer et al, 2016).…”
Section: Figmentioning
confidence: 99%
“…However, when expressed from its native locus and promoter, GFP-tagged TFP1 was not evident in asexual blood-stage parasites and the recombinant transporter was instead localised to the osmiophilic body of gametocytes and the micronemes and surface of sporozoites (Kehrer et al, 2016). Moreover, tfp1 was shown to be dispensable in the asexual blood stage, but was essential for infecting mosquitos -and this knockout phenotype was rescued by mCherry-tagged TFP1 (Kehrer et al, 2016). The latter findings also concurred with the detection of TFP1 in proteomic screens of gametocytes and sporozoites as well as its absence from a proteomic screen of asexual blood-stage parasites (Lasonder et al, 2008;Silvestrini et al, 2010;Lindner et al, 2013).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation